2017
DOI: 10.1038/s41598-017-16158-y
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile changes in the jejunum of weaned piglets after oral administration of Lactobacillus or an antibiotic

Abstract: The small intestine plays an essential role in the health and well-being of animals. Previous studies have shown that Lactobacillus has a protective effect on intestinal morphology, intestinal epithelium integrity and appropriate maturation of gut-associated tissues. Here, gene expression in jejunum tissue of weaned piglets was investigated by RNA-seq analysis after administration of sterile saline, Lactobacillus reuteri, or an antibiotic (chlortetracycline). In total, 401 and 293 genes were significantly regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
(40 reference statements)
1
8
0
Order By: Relevance
“…Moreover, an analysis of the LCFAs profiles of piglets also revealed that the PUFAs C18:2n6c, C18:3n3, C20:4n6, and C22:6n3 were significantly higher in the L. reuteri ZLR003 group compared with the control group. This is consistent with our finding from a previous study that the PUFAs C18:2n6c, C18:3n3, and C20:4n6 in the colon were significantly higher in the L. reuteri group compared with the control group (Zhang D.Y. et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, an analysis of the LCFAs profiles of piglets also revealed that the PUFAs C18:2n6c, C18:3n3, C20:4n6, and C22:6n3 were significantly higher in the L. reuteri ZLR003 group compared with the control group. This is consistent with our finding from a previous study that the PUFAs C18:2n6c, C18:3n3, and C20:4n6 in the colon were significantly higher in the L. reuteri group compared with the control group (Zhang D.Y. et al, 2017).…”
Section: Discussionsupporting
confidence: 94%
“…Our previous work showed that this strain affected the gut microbiota composition in the jejunum, colon, and cecum of weaned piglets (Zhang et al, 2016). In addition, the results of Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis by RNA-seq in the jejunum tissue showed that the expression of genes related to arachidonic acid metabolism and linoleic acid metabolism, glutathione metabolism, glycine, and serine and threonine metabolism were improved after treatment with L. reuteri ZLR003 compared with the control group (Zhang D.Y. et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This observation is consistent with the previously reported ability of lactobacilli to induce Nrf2-ARE and GPX2 expression. Such effect was observed both in vitro in mouse embryotic fibroblast and NIT-3T3 cells, using Lactobacillus gasseri or metabolites from L. plantarum on HepG2 cells, and in vivo in pig’s jejunum, using Lactobacillus reuteri ( 50 52 ). Another in vivo study conducted with diabetic patients demonstrated that consumption of yogurt containing probiotics ( Lactobacillus acidophilus La5 and Bifidobacterium lactis Bb12) for 6 weeks was able to influence the oxidative status in type 2 diabetic patients, inducing decreased fasting blood glucose and glycated hemoglobin and increased activities of SOD and GPX2, and total antioxidant status compared with the control yogurt group without probiotics ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal tract is susceptible to various stresses, such as weaning in early life and challenges with pathogenic bacteria or toxins. Because intestinal dysfunction caused by various stresses is directly related to growth performance in pigs, affecting parameters such as feed intake, average daily gain, and gain/feed ratio, it is important to consider a variety of environmental factors, including diets and stressors, to maintain intestinal health 10,11 . The fact that bioactive food compounds in the diet can directly interact with genes and affect transcription factors, protein expression, and metabolite production has led to nutritional research in livestock 12 .…”
Section: Discussionmentioning
confidence: 99%